Molecular Analysis of MEFV Gene Polymorphisms and Mutations in Iranian Azeri Patients with Rheumatoid Arthritis - Alireza KHABBAZI; Farideh ZOLRAHIM; Mehrdad ASGHARI ESTIAR; Ebrahim SAKHINIA; Sousan KOLAHI (Tehran University of Medical Sciences, 2016)
Molecular Analysis of MEFV Gene Polymorphisms and  Mutations in Iranian Azeri Patients with Rheumatoid Arthritis